A rare sequence variant in intron 1 of THAP1 is associated with primary dystonia. Issue 3 (11th February 2014) - Vemula, Satya R.; Xiao, Jianfeng; Zhao, Yu; Bastian, Robert W.; Perlmutter, Joel S.; Racette, Brad A.; Paniello, Randal C.; Wszolek, Zbigniew K.; Uitti, Ryan J.; Van Gerpen, Jay A.; Hedera, Peter; Truong, Daniel D.; et al.
Abstract Although coding variants in THAP1 have been causally associated with primary dystonia, the contribution of noncoding variants remains uncertain. Herein, we examine a previously identified Intron 1 variant (c.71+9C>A, rs200209986). Among 1672 subjects with mainly adult‐onset primary dystonia, 12 harbored the variant in contrast to 1/1574 controls (P < 0.01). Dystonia classification included cervical dystonia (N = 3), laryngeal dystonia (adductor subtype, N = 3), jaw‐opening oromandibular dystonia (N = 1), blepharospasm (N = 2), and unclassified (N = 3). Age of dystonia onset ranged from 25 to 69 years (mean = 54 years). In comparison to controls with no identified THAP1 sequence variants, the c.71+9C>A variant was associated with an elevated ratio of Isoform 1 (NM_018105) to Isoform 2 (NM_199003) in leukocytes. In silico and minigene analyses indicated that c.71+9C>A alters THAP1 splicing. Lymphoblastoid cells harboring the c.71+9C>A variant showed extensive apoptosis with relatively fewer cells in the G2 phase of the cell cycle. Differentially expressed genes from lymphoblastoid cells revealed that the c.71+9C>A variant exerts effects on DNA synthesis, cell growth and proliferation, cell survival, and cytotoxicity. In aggregate, these data indicate that THAP1 c.71+9C>A is a risk factor for adult‐onset primary dystonia.